Shaping Potential of Manual NiTi K-File and Rotary ProTaper and Using CT to Analyze the Shaped Canals Final Outcome (International Journal of Food and Nutritional Sciences, 2022)
To assess and compare the shaping potential of manual NiTi K-files and Rotary ProTaper instruments in narrow canals using CT. Materials and method: Fifty freshly extracted permanent maxillary molars (1st and 2nd), 30 were selected with curvatures (20 to 40°) (Schneider 1971). The teeth were cleaned and stored in normal saline until used. All the mesiobuccal canals were scanned by CT to obtain preinstrumented images and randomly divided into two groups with 15 samples each. Group I (ProTaper Rotary): Canals were instrumented with Protaper Rotary instruments using crown down technique according to manufacturer’s instructions. Group II (NiTi K-file): Were instrumented by NiTi K-files using step back technique with a quarter turn/pull motion. Comparative evaluations of working time was done for both the experimental groups. CT analysis and measurements: The samples were analyzed and evaluated for: • Postinstrumentation change in volume and cross-sections area. Result: From the observations and statistical analysis carried out in this study, it was found that: There was a statistically significant difference between all the parameters judged for the present study that is: 1. Instrumentation with ProTaper Rotary system took significantly less time than instrumentation with manual NiTi K-file. 2. Change in the canal volume following instrumentation with ProTaper Rotary was significantly greater than that produced by manual NITi K-file. 3. a. Change in cross-section area at 2 and 3 mm from the apex was significantly greater with manual NiTi K-file as compared to ProTaper Rotary. b. Change in cross sections at 4.5, 6 and 7.5 mm from the apex with ProTaper Rotary was significantly greater than that produced by manual NITi K-file. Conclusion: This clearly establishes that there is a drastic difference in the shaping ability of manual and Rotary NiTi instruments used with step back and crown down technique respectively with the rotary instrumentation being faster and producing greater changes in the canal anatomy.